An investigation of lymphovenous communications in the upper limbs of breast cancer patients. Issue 3 (March 2015) - Bains, S.K.; Ballinger, J.; Allen, S.; Stanton, A.W.B.; Levick, J.R.; Mortimer, P.S.; Purushotham, A.D.; Peters, A.M.
Abstract Background Approximately 25% of breast cancer patients who undergo treatment to the axilla develop breast cancer-related lymphoedema (BCRL). The aim of this study was to test the hypothesis that lymphovenous communications (LVCs) open and act as a protective mechanism against the development of BCRL. Methods Five patients (Group 1) received intradermal injections of 99mTechnetium-labelled autologous erythrocytes into the 2nd ipsilateral hand webspace before and 6–12 weeks following axillary node clearance surgery (ANC). Ten patients at least three years after ANC were also recruited (Group 2); seven had developed BCRL and three had not. Blood was sampled from ipsilateral and contralateral antecubital veins 5, 15, 30, 60, 120 and 180 min post-injection to assess pre-nodal shunting from lymph to blood (LVCs), since nodes block erythrocyte transit. The proportion of activity remaining in the depot was used to calculate the degree of shunting in those with evidence of LVCs. Results Significant erythrocyte-bound activity, increasing over time, was detected contralaterally in 3 of the 5 patients from Group 1 (none of whom developed BCRL) and 3 of 7 patients with BCRL from Group 2, which indicated the presence of LVCs. The degree of shunting was more marked in those patients who did not develop BCRL compared with those who did. Conclusions The time-course of erythrocyte-bound contralateral activity indicates transit through lymphovenous communications rather than needle-induced trauma. Lymphovenous communications large enough to transmit erythrocytes are probably constitutional rather than induced. A larger study is warranted to assess any resulting protection against BCRL.